Usefulness of the BIG Score in Predicting Massive Transfusion and In-Hospital Death in Adult Trauma Patients - Sejun Park; Il Jae Wang; Seok-Ran Yeom; Sung-Wook Park; Suck Ju Cho; Wook Tae Yang; Wonwoong Tae; Up Huh; Chanhee Song; Yeaeun Kim; Jong-Hwan Park; Youngmo Cho (Emergency Medicine International)
The base deficit (B), international normalized ratio (I), and Glasgow coma scale (GCS) (BIG) score is useful in predicting mortality in pediatric trauma patients; however, studies on the use of BIG score in adult patients with trauma are sparse. In addition, studies on the correlation between the BIG score and massive transfusion (MT) have not yet been conducted. This study aimed to evaluate the predictive value of BIG score for mortality and the need for MT in adult trauma patients. This retrospective study used data collected between 2016 and 2020 at our hospital’s trauma center and registry. The predictive value of BIG score was compared with that of the Injury Severity Score (ISS) and Revised Trauma Score (RTS). Logistic regression analysis was carried out to assess whether BIG score was an independent risk factor. Receiver operating characteristic (ROC) curve analysis was performed, and predictive values were evaluated by measuring the area under the ROC curve (AUROC). In total, 5,605 patients were included in this study. In logistic regression analysis, BIG score was independently associated with in-hospital mortality (odds ratio (OR): 1.1859; 95% confidence interval (CI): 1.1636–1.2086) and MT (OR: 1.0802; 95% CI: 1.0609–1.0999). The AUROCs of BIG score for in-hospital mortality and MT were 0.852 (0.842–0.861) and 0.848 (0.838–0.857), respectively. Contrastingly, the AUROCs of ISS and RTS for in-hospital mortality were 0.795 (0.784–0.805) and 0.859 (0.850–0.868), respectively. Moreover, AUROCs of ISS and RTS for MT were 0.812 (0.802–0.822) and 0.838 (0.828–0.848), respectively. The predictive value of BIG score for mortality and MT was significantly higher than that of the ISS. The BIG score also showed a better AUROC for predicting in-hospital mortality compared with RTS. In conclusion, the BIG score is a useful indicator for predicting mortality and the need for MT in adult trauma patients.